PENGARUH MEKANISME GCG DAN PELAPORAN CSR TERHADAP NILAI PERUSAHAAN DI BEI - Ardyanto, Ferry Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the influence of good governance mechanism and the reporting of corporate social responsibility to the companyâs value. The companyâs value in this research is proxy by Tobinâs Q value. The selection of samples is performed by using purposive sampling method to the food and beverages companies which are listed in the Indonesia Stock Exchange from 2007 to 2011. As many as 11 food and beverages companies are used as samples in this research. The multiple regressions are applied as method of analysis in this research. The result of this research indicates that the board of commissioners, public ownership, managerial ownership and the reporting of corporate social responsibility variables has significant influence to the companyâs value. Keywords:Companyâs Value, Board of Commissioners, Public Ownership, Management Ownership, Institutional Ownership, and Corporate Social Responsibility.